Evaluation of Character Education Programsat 3 Air Kumbang State First Middle School - Widodo, Edi; Harapan, Edi; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The research objective was to determine and describe the evaluation of character education in SMP Negeri 3 Air Kumbang. The research used in this research is the evaluation of the CIPP model. The primary data sources were from the first informants, namely the principal, homeroom teacher, teacher, students and parents of students of SMP Negeri 3 Air Kumbang. Data collection tools are observation, documentation, interviews and questionnaires. The results of the study can be concluded that the attitudes and behavior of students who show on the religious side, the inculcation of character about honest behavior in students is 86.25% and declared successful, the attitudes and behavior of students who show the character of discipline on average the percentage is 46.25% Thus it can be concluded that the character planting of discipline in students is 80% declared successful, the attitudes and behavior of students who show their concern for the environment have an average percentage of success, those there were 13.75% and